Antibacterial Activity of Gaultheria procumbens, Thymus vulgaris, Peganum harmala, and Bergamot (Citrus bergamia) Essential Oils against Enterococcus raffinosus Isolated from Urinary Tract Infections (World Journal of Experimental Biosciences, 2025)
The discovery of alternative antimicrobial agents against resistant bacteria has been a major target for microbiologists and physicians, especially in recent years, because the resistance to antibiotics has increased. No previous study has investigated the antibacterial effects of essential oils prepared from Gaultheria procumbens, Thymus vulgaris, Peganum harmala, and Bergamot (Citrus bergamia) against Enterococcus raffinosus. The present study aims to investigate the antibacterial activity of the essential oils of the above medicinal plants against E. raffinosus in vitro. In the present study, essential oils were extracted from the above four medicinal plants. For evaluating the antibacterial effect of the essential oils, three isolates of E. raffinosus were isolated from 44 urine samples collected from patients with urinary tract infections (UTIs). Only one isolate was multidrug-resistant (MDR) to commonly used antibiotics. The microdilution method on microtiter plates and the agar diffusion method were used to check the susceptibility of E. raffinosus to the essential oils. The study showed that the essential oil of T. vulgaris showed the highest antibacterial activity against E. raffinosus, followed by P. harmala. The present study showed a moderate antibacterial effect of G. procumbens essential oil against E. raffinosus. The present study showed no antibacterial effect of the essential oil of Bergamot against E. raffinosus. It can be concluded from the study that the antibacterial effect of the essential oils prepared from G. procumbens, T. vulgaris, and P. harmala against MDR-E. raffinosus, that is why these oils can serve as a novel antibacterial agent against E. raffinosus infections.